AUDITORÍA DE CUMPLIMIENTO AL PLAN DE MANEJO AMBIENTAL A LA CENTRAL TÉRMICA DE CATAMAYO DE LA EMPRESA ELÉCTRICA REGIONAL DEL SUR S.A., PERIODO 2022 - Cañart Espinoza, Daniela Damaris (2024)
The Curricular Integration work entitled “Compliance Audit of the Environmental Management Plan for the Catamayo Thermal Power Plant of Empresa Eléctrica Regional del Sur S.A, Period 2022”, was developed as a requirement prior to obtaining the title of Bachelor of Accounting and Auditing. based on the following objectives: the identification of environmental legal requirements based on the environmental management plan of the Catamayo Thermal Power Plant; determine the degree of compliance with the legal provisions and environmental regulations applicable to the plant and prepare the final environmental audit report that includes the respective comments, conclusions and recommendations based on the findings obtained, to guide the making of correct decisions and the improvement of the entity's environmental management. The procedure was framed according to what is indicated in the Environmental Management and Control Manual of Dr. Fernando Bustos, which includes Phase I: Planning or Pre-audit, which began with a prior diagnosis of information collection, determination of critical areas and determination of procedures. to be applied in the execution phase; Phase II “In-situ” Audit, the matrices were prepared to determine the degree of compliance with the environmental legal provisions, followed by making the narrative records according to the deficiencies found; Phase III: Communication of Results, the Audit Report was prepared; which is composed of the respective comments, conclusions and recommendations of the deficiencies found such as: cleaning of the interior and exterior of the facilities is not carried out, existence of scrap metal within the facilities and it is not located in a designated place with its respective signage, the formation of weeds and excessive grass, waterlogging due to inadequate drainage, the first aid kit does not have the necessary equipment, there is deterioration in some individual containers for the collection of non-hazardous solid waste and not all of them have a lid and cover, Safety Plan Outdated Environmental Management.